If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(a + 1) + 4(2a + -3) = 0 Reorder the terms: 3(1 + a) + 4(2a + -3) = 0 (1 * 3 + a * 3) + 4(2a + -3) = 0 (3 + 3a) + 4(2a + -3) = 0 Reorder the terms: 3 + 3a + 4(-3 + 2a) = 0 3 + 3a + (-3 * 4 + 2a * 4) = 0 3 + 3a + (-12 + 8a) = 0 Reorder the terms: 3 + -12 + 3a + 8a = 0 Combine like terms: 3 + -12 = -9 -9 + 3a + 8a = 0 Combine like terms: 3a + 8a = 11a -9 + 11a = 0 Solving -9 + 11a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 11a = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 11a = 0 + 9 11a = 0 + 9 Combine like terms: 0 + 9 = 9 11a = 9 Divide each side by '11'. a = 0.8181818182 Simplifying a = 0.8181818182
| 2x^2-9x^2+7x+6=0 | | (6u^2-2u+2)+(-7u^2-3u+5)-(-9u^2+5u-3)= | | 7p-4=29+2p | | 29=14x-8 | | 4(u+2u)=8u+30 | | 12-18=6z | | x^2-2x+2=4 | | 2v+4v=42 | | -24x+36=2x | | g=d+e+f | | 1.2-4.3a-3.1a=-14.34 | | 15.3y=0.08 | | 7y=7y+7 | | (y+11)12= | | -10=-2x+5x-7 | | 1+7n-18=-9 | | 2x-4-5x+6= | | (u+10)12= | | 2m(m+2)=0 | | 15=10-x4 | | 12(v-9)= | | 4y^2-6=-58 | | h(x)=4x^2+x-5 | | 3.2x=0.064 | | 7x=81-2x | | 15x-2=-3 | | 2.5(x+2)+4.5+1.5(-3)=15 | | -3(2y-2y)-y=-3(y-3) | | 0.6(10n-3)=-1.5(n+2)-0.3 | | (v+10)12= | | -(5a+6)=-4(-f+2) | | 2x+2=161 |